Recent Advances, New Perspectives and Applications in the Treatment of Ovarian Cancer - Friedrich, Michael (IntechOpen, 2023)
Recent Advances, New Perspectives and Applications in the Treatment of Ovarian Cancer is a review of interesting and clinically important advances in the tumor biology and treatment of ovarian cancer. Major aspects of scientific progress in the treatment of ovarian cancer are covered, focusing on new knowledge due to advances in molecular techniques, understanding of tumor biology and innovative new treatment options. An interesting collection of innovations in the treatment of ovarian cancer and opinions from specialists in this field from around the world are brought together in this book.